Gas sensing selectivity of SnO2-xNiO sensors for homogeneous gases and its selectivity mechanism: Experimental and theoretical studies - Yin, Xi-Tao; Dastan, Davoud; Gity, Farzan; Li, Jing; Shi, Zhicheng; Alharbi, Najlaa D.; Liu, Ying; Tan, Xiao-Ming; Gao, Xiao-Chun; Ma, Xiao-Guang; Ansari, Lida (Sensors and actuators. A. Physical., 2023)
Although the MOS gas sensors are widely employed to detect gas owing to the excellent sensing performance in fast response and recovery time and high sensitivity. However, the poor selectivity is among the most severe challenge to determine the homogeneous gases, especially when CO and H2 coexist. The sensors have the same gas sensing response to homogeneous gases, which attribute to the cross-sensitivity. Herein, a facile sol-gel method has been used to prepare SnO2-xNiO composites and the sensing performances of sensors are further investigated using XRD, TEM, XPS. The experimental results indicate that the selectivity of SnO2-based gas sensor to CO and H2 can be improved by modulating electron and hole concentration in the p-n composites. Interestingly, the gas sensing results show that SnO2-3.58NiO sensor annealed at 550 °C worked at 350 °C presents opposite sensing response to homogeneous gases CO and H2, that is, p-type response to CO but n-type to H2. Insight into the interactions between CO and H2 target gas molecules with SnO2 and NiO surfaces in addition to the target gas-dependent modulation of SnO2 and NiO conductivity are investigated through density functional theory calculations supporting the experimental results. The opposite gas sensing behavior of the SnO2-3.58NiO composites to both gases suggests that the SnO2-3.58NiO composite can distinguish between CO and H2. This paper provides an approach to effectively enhance this type gas sensor selectivity. [Display omitted] •SnO2-xNiO heterojunction gas sensors are fabricated that show a p-type and an n-type response to H2 and CO, respectively.•The opposite sensing mechanism of SnO2-xNiO NPs to CO and H2 is proposed experimentally and theoretically.•First report on optimized band structures of NiO and SnO2 thin films with corrected bandgaps, enabling conductivity modulation and sensing analysis.•Atomistic scale insight into the interactions between the target molecules and the sensing materials is provided.•Excellent agreement between the experimental nanoscale observations and the atomic-scale first principle simulations are achieved.